Cavitation and its combinations with other advanced oxidation processes in phenol wastewater treatment: a review - Sukhatskiy, Yurii Viktorovych; Сухацький, Юрій Вікторович; Znak, Zenovii Orestovych; Знак, Зеновій Орестович; Zin, Olha Ivanivna; Зінь, Ольга Іванівна (ДВНЗ "Український державний хіміко-технологічний університет", 2020)
The review provides a systematic understanding of the mechanism of the sonochemical degradation of phenol. It was shown that the main contribution to the sonochemical degradation of phenol, a hydrophilic non-volatile wastewater component, is related to hydroxylation on the boundary of the «cavitation bubble–water contaminant solution». Depending on the method of generating hydroxyl radicals, all wastewater treatment methods for phenol removal based on advanced oxidation processes are classified into the following categories: chemical (acoustic and hydrodynamic cavitation, use of oxidants, Fenton process, and Fenton-like processes), photochemical (photolysis and photocatalysis), electrochemical and combined techniques. The essence of these methods is revealed and their main advantages and disadvantages are reviewed. It is shown that the efficiency of combined methods of phenol degradation that are based on the use of cavitation (acoustic or hydrodynamic) depends on the power of ultrasonic emitters, the frequency of ultrasonic vibrations, the magnitude of the pressure at the inlet of the hydrodynamic cavitator, physicochemical properties of media (temperature and pH), initial phenol concentration in aqueous medium, the design features of the cavitation generators, the presence of water-soluble gases or solid particles that exhibit catalytic properties, and the consumption of oxidizing reagents. Literature data showed that the most cost-effective method involving the use of ultrasonic cavitation is a combination «ultrasonic cavitation+photolysis+ozonation». The choice of a particular method for the degradation of phenol is determined by its content in wastewaters and their volume, the required degree of degradation, the duration of the purification process (the rate of degradation of the phenol), and economic indicators.

В огляді систематизовано теоретичні уявлення про механізм сонохімічної деградації фенолу. Зазначено, що основний внесок у сонохімічну деградацію фенолу, як гідрофільного нелеткого компонента стічних вод, належить гідроксилюванню на межі "кавітаційна бульбашка-водний розчин забруднювача". Залежно від способу генерування гідроксильних радикалів всі методи очищення стічних вод від фенолу, засновані на передових процесах окислення, класифіковано на хімічні (акустична та гідродинамічна кавітація, використання реаґентів-окисників, процес Фентона та Фентон-подібні процеси), фотохімічні (фотоліз, фотокаталіз), електрохімічні та комбіновані. Розкрито сутність цих методів, описано їх основні переваги та недоліки. Показано, що ефективність комбінованих методів деградації фенолу, що базуються на використанні кавітації (акустичної або гідродинамічної), залежить від потужності ультразвукових випромінювачів, частоти ультразвуку, величини тиску на вході у гідродинамічний кавітатор, фізико-хімічних властивостей середовищ (температури, pH), початкової концентрації фенолу у водному середовищі, конструктивних особливостей генераторів кавітації, наявності розчинених у воді газів або твердих частинок, які виявляють каталітичні властивості, витрати реаґентів-окисників. На основі порівняльного оцінювання витрат на очищення феноловмісних стічних вод виявлено, що найбільш економічно вигідним методом, який базується на використанні ультразвукової кавітації, є комбінація "ультразвукова кавітація+фотоліз+озонування". Встановлено, що застосування того чи іншого методу для деградації фенолу буде зумовлено його вмістом у стоках, об'ємом стоків, необхідним ступенем деградації, тривалістю процесу очищення, що визначається швидкістю деградації фенолу, та економічними показниками.
Кавітація та її комбінації з іншими передовими процесами окислення для очищення стічних вод від фенолу: огляд
Keywords: cavitation; кавітація; phenol; фенол; hydroxyl radicals; гідроксильні радикали; ultrasound; ультразвук; Fenton process; процес Фентона; photolysis; фотоліз; photocatalysis; фотокаталіз; 620.193.16:628.316.12:547.562.1